Women’s Represantation in The Novel of Sali: Kisah Seorang Wanita Suku Dani By Dewi Linggasari - Inayah, Laelatul; Aqidho, Yoga Ayudha (AJIRSS: Asian Journal of Innovative Research in Social Science, 2023)
This research discusses the novel entitled Sali: Kisah Seorang Wanita Suku Dani by Dewi Linggasari using representation theory. This research aims to represent the role of Dani tribal women in relation to the customs and culture that the Dani tribal community still adheres to, one of which is patriarchal culture. This research also uses cultural studies studies related to the relationship between understanding and representation theory. The main data used in this research are several narrative descriptions and dialogues in the novel entitled Sali: Kisah Seorang Wanita Suku Dani, which was first published in 2007 by the publisher Kunci Ilmu Yogyakarta. This research was conducted without prioritizing numbers, but using a depth of appreciation for the interactions between concepts being studied empirically. This research aims to reveal forms of injustice that are reflected through: 1) The Position of Women, 2) Women's Struggle, and 3) The language used to represent women in the novel Sali: Kisah Seorang Wanita Suku Dani by Dewi Linggasari.